PENGEMBANGAN MEDIA PAPAN SUMBER DAYA ALAM ORIGINAL PADA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Muhammad Andra Pratama; Bukman Lian; Kiki Aryaningrum (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
The aim is to produce original natural resource board learning media for Class IV Elementary School social studies learning that is valid, practical and has potential effects. This type of research and development uses (Research and Development) using the ADDIE model which consists of 5 stages, namely, 1) Analyze, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The subjects in this research were 3 media, language and material validators, and 3 students in class IV elementary school, one to one and a small group of 8 students. Data collection instruments include media validation sheets by validators, practical questionnaire sheets from students and documentation. Based on the research results, the average obtained by experts was 84.4% with a very valid category, from the results of the questionnaire the student responses were 93% one to one and 90% for small groups with a very practical category, and the results of the test questions with a result of 86 .6% with very potential effect category. Based on validation results, practical results and potential effect results, it is concluded that this Original Natural Resource is very suitable for use in Indonesian language learning. Keywords: Board Original Natural Resources